Design and Fabrication of Ultrathin Metallic Phase Shifters for Visible and Near-Infrared Wavelengths - Qing Guo; Jinkui Chu; Chuanlong Guan; Chuxiao Zhang; Ran Zhang (Micromachines)
The polarization state of light is critical for biological imaging, acousto-optics, bio-navigation, and many other optical applications. Phase shifters are extensively researched for their applications in optics. The size of optical elements with phase delay that are made from natural birefringent materials is limited; however, fabricating waveplates from dielectric metamaterials is very complex and expensive. Here, we present an ultrathin (14 nm) metallic phase shifter developed using nanoimprinting technology and the oxygen plasma ashing technique for visible and near-infrared wavelengths. The fabrication process can produce desirable metallic phase shifters with high efficiency, large area, and low cost. We demonstrate through a numerical simulation and experiment that the metallic phase shifter exhibits phase delay performance. Our results highlight the simplicity of the fabrication process for a metallic phase shifter with phase delay performance and offer important opportunities for creating high-efficiency, ultrathin polarizing elements, which can be used in miniaturized devices, such as integrated circuits.